Penguatan Pemahaman Geologi Mahasiswa Pendidikan Geografi UMS melalui Edukasi BRIN Karangsambung sebagai Kawasan Geodiversitas - Arief Rahman Husein; Mukminan Mukminan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Geology is a branch of geography that studies tectonic processes inside and outside the earth's surface. The Karangsambung area is a geological area where a research center (BRIN Karangsambung) is located. Strengthening efforts provide geospatial understanding and literacy regarding material on geology in general and regional geology, as well as material on geoparks. The goal is that students are expected to be able to expand their knowledge and understanding so that students are able to apply geological scientific concepts comprehensively, especially in life. The method used in this study uses a descriptive qualitative method, the type of research is phenomenology and the approach used through field observation and interviews. The results of this study explain that PKL Geography Education students, UMS, get a geological study process and observational learning methods that are able to strengthen the understanding of geological science. This activity provides relevant understanding and knowledge about geological studies, to be applied in lectures and studies related to geographical studies as a discipline that continues to develop and experience renewal.